Use of Modern IT Technologies in Marketing for Manufacturers and Service Providers - Azamat Tuigunovich, Ziyadullaev Akmalzhon ugli , Azamat, Abdurakhim; Ziyodullayev, Abdurahim (THE INNOVATION ECONOMY, 2024)
Currently, information technology (it) has become an integral part of any organization, whether it be a large holding company or a small business. When entering the market, information technology is used to increase efficiency, optimize business processes, create new products and services, increase profits and reduce costs. Modern business technologies can significantly speed up work, increase the efficiency and accuracy of tasks. In a fast-paced and digital world, the role of technology in reaching the market has become more important than ever. The article explores how to increase efficiency with information technology in the market, optimize business processes, create new products and services, increase profits and reduce costs, transform the transformative power of modern IT technologies and how it allows businesses to reach, engage and transform a target audience through modern marketing in the digital age, and optimize marketability. As a result of the study and research, proposals and practical recommendations were made to introduce it technologies for trading network portal, retail and hypermarkets through IT outsourcing to the activities of manufacturers, enterprises and companies in our Republic using foreign experience